ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL (RGEC) YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) (Studi Kasus Pada PT. Bank Syariah Indonesia (Persero) Tbk Periode 2021 - 2023) - Sri Ratna Ayu; Ihwan Satria Lesmana; Ombi Rimli (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The banking industry is very important in economic development, increasing economic growth, equality and stability of the country. (Nufus et al., 2019). With so many financial institutions and increasingly tight competition in the banking world, financial institutions must be able to compete well by paying attention to the health of the bank.This research aims to find out the level of bank health at PT. Bank Syariah Indonesia (Persero) Tbk uses the RGEC method. This research method is descriptive research with a qualitative research type. The data source is secondary data.The results of research on the health level of PT Bank Syariah Indonesia (Persero) Tbk for the 2021-2023 period, seen from the Risk Profile factor component using the Non-Performing Financing ratio and from the Good Corporate Governance factor component, it received a healthy predicate, the Financing to Deposit Ratio received a very healthy predicate in 2021. 2021 and a healthy predicate in 2022-2023, the Earnings factor using the Return On Assets ratio gets a very healthy predicate in 2021-2023, and finally the Capital factor component using the Capital Adequacy Ratio in 2021-2023 gets a very healthy predicate. Based on the results of research at PT Bank Syariah Indonesia (Persero) Tbk for the 2021-2023 period using the RGEC method, it was concluded that BSI's health level was at PK-1 for 2021 (Very Healthy) with a ratio of 92%. And in 2022-2023 it will be at PK-1 (very healthy) with a ratio of 88%.